DEVELOPMENT AND APPLICATIONS OF ECO-INNOVATION RISK ANAL-YSIS MEASURES FOR GREEN BUILDINGS - Liliya Hogaboam, Liliya Hogaboam (Forestry, Forest, Paper and Woodworking Industry, 2024)
Eco-innovations – new developments in products, services and processes which consider ecological knowledge and effect in their commercial applications – could bring new risks to the product or project life cycle. This paper introduces measures for evaluation of possible risks versus values added by eco-innovative novelties. Additional risk measures, incorporating probabilities and severities of risks, proposed could be useful in certain situations of risk analysis. E/R measure was tested in two cases of green buildings: Courthouse Square in Salem, Oregon and AMD Lone Star in Oak Hill, Austin, Texas. Microsoft Excel was used for E/R measure matrix. I would like to acknowledge contributions of Türkay Dereli1, Alptekin Durmuşoğlu, Tuğrul U. Daim, Manar Al mallak2, Sajeda Tamimi2 and Bahareh Vossoghi2 to the research presented in this paper.